Foreign Bank Subsidiaries' Default Risk During the Global Crisis : What Factors Help Insulate Affiliates from Their Parents? - Anginer, Deniz; Cerutti, Eugenio; Martinez Peria, Maria Soledad (World Bank Group, Washington, DC, 2014)
This paper examines the association between the default risk of foreign bank subsidiaries and their parents during the global financial crisis, with the purpose of understanding what factors can help insulate affiliates from their parents. The paper finds evidence of a significant positive correlation between parent banks' and foreign subsidiaries' default risk. This correlation is lower for subsidiaries that have higher capital, retail deposit funding, and profitability ratios and that are more independently managed from their parents. Host country regulations also influence the extent to which shocks to the parents affect the subsidiaries' default risk. In particular, the correlation between the default risk of the subsidiary and the parent is lower for subsidiaries operating in countries that impose higher capital, reserve, provisioning, and disclosure requirements and tougher restrictions on bank activities.